The mirage of 'Arabrew': Ideologies for understanding Arabic-Hebrew contact - Hawker, N (Cambridge University Press, 2018)
‘Arabrew’ denotes a mixture of the languages that index two nations known for their seemingly intractable conflict. It is supposedly spoken by Palestinians and other Arabs who are citizens of Israel. Evidence from the field gathered in 2015 shows some codeswitching, especially inter-sentential, and borrowing, mostly of nouns for specialist terminology, and of a few discourse markers. This does not support the claim that a new variety has emerged, yet the debate around it channels concerns about nonlinguistic issues relating to the political economy of Israel and to anxieties about Israeli-Palestinian relations. This debate invokes ideologies, including language ideologies, of nationalism, colonialism, liberalism, and more, that are identifiably linked to the historical and material contexts. The study uses critical discourse analysis and contact linguistics to outline the articulation between distinctions of national identity, socioeconomic class, the way people speak, and the way this speech is ideologically received. (Arabic, Hebrew, codeswitching, ideology)*